Insulin Resistance in Association with Metabolic Syndrome in Wasit University Students in Iraq - Alaa Zamil; Seenaa Amin (College of Pharmacy University of Baghdad, 2023)
In Iraq 1.4 million of people have diabetes, the prevalence of T2DM was ranged (8.5%-13.9%), and the cluster of metabolic abnormalities has long been identified as the risk factors for type 2 diabetes and is now commonly described as metabolic syndrome/MetS. Insulin resistance takes a key role in the process of the MetS and has even been hypothesized as its underlying cause. Clinical and epidemiologic studies also indicate that obesity and life style habit might be correlated with IR. This study examined the relationship between IR and MetS in a sample of young, healthy university students in Iraq. It discovered that the severity of IR is positively correlated with the clustering of MetS risk factors in Iraqi students, suggesting that the IR index could be used as a diagnostic tool to identify the young adult who is at higher risk of developing IR and help prevent metabolic disorders that may develop secondary to IR. Insulin resistance was highly correlated with dietary product use, high BMI, and physical inactivity, investigating the IR in an early stage is crucial for trying to stop the disease progression into chronic disease.